Assessment of Bunyavirales activity and circulation in humans, livestock, and peri-domestic rodents in diverse ecologies in Kenya, 2020-2022 - Venter, Marietjie (University of Pretoria, 2023)
Thesis (PhD (Medical Virology))--University of Pretoria, 2023.